Obstacle avoidance algorithm for swarm of quadrotor unmanned aerial vehicle using artificial potential fields - Galvez, Reagan L. (Animo Repository, 2017)
Unmanned aerial vehicle that is moving from one place to another needs to have a real-time obstacle avoidance controller to prevent collisions in the obstacles around it. In this paper, the concept of artificial potential field is proposed to implement obstacle avoidance in swarm of quadrotors. This is based on the assumptions that the target and obstacle will introduce a certain force that will direct the robot to its destination. The effectiveness of this method was tested in a computer simulation and verified using real quadrotors. © 2017 IEEE.